Opening doors to participation of youth with physical disabilities: An intervention study: Favoriser la participation des adolescents ayant des handicaps physiques : Étude d'intervention. (April 2016) - Anaby, Dana R.; Law, Mary C.; Majnemer, Annette; Feldman, Debbie
Background: While participation in leisure activities is beneficial to youth's health, little is known about effective intervention strategies to promote participation. Purpose: The aim of this study was to examine the effectiveness of environment-based interventions on participation of youth with physical disabilities. Method: Six adolescents ages 14 to 17 years participated in a 12-week intervention aimed at removing environmental barriers and coaching parents. An interrupted time series design was employed and a systematic replication of the intervention effect was examined across three individualized participation goals and across participants (17 goals overall). Goal performance was measured repeatedly using the Canadian Occupational Performance Measure and analyzed using visual inspection and a celeration line approach. Findings: A clinically significant improvement in performance scores ( M = 4.5, SD = 1.77) was observed across all 17 goals, and a statistically significant treatment effect was replicated in 13 goals (76%). Implications: Findings support the effectiveness of environment-based interventions in promoting youth participation, but larger studies are required.